Research by Psychiatric Trainees and Early Career Psychiatrists—Results of a Survey From 34 Countries in Europe - Koelkebeck, Katja; Andlauer, Olivier; Asztalos, Marton; Jovanovic, Nikolina; Kazakova, Olga; Naughton, Sean; Pantovic-Stefanovic, Maja; Riese, Florian; Pinto da Costa, Mariana (Frontiers in Psychiatry, 2021)
Clinical psychiatric practice should be intricately linked with research work. Although psychiatric trainees and early career psychiatrists (ECPs) are in the frontline of clinical services, little is known about how much access they have to research opportunities. A semi-structured questionnaire of 35 questions – exploring research goals achieved, facilitators and barriers as well as personal context – was sent to psychiatric trainees and ECPs across Europe. The survey was disseminated through the local committees of the main professional psychiatric societies in Europe. A total of 258 individuals working in 34 European countries participated. The majority (69.8%) were psychiatric trainees within training in adult psychiatry. Most participants (69.0%) were highly interested in research, but faced major obstacles towards their research activities, such as lack of time and funding. They were highly satisfied with mentoring and publishing papers. Only half of the participants, however, had already published a scientific article, and only a few have been able to contribute to randomized clinical trials (20.9%). A large proportion of participants (87.2%) reported to conduct research after or during a mixture of working hours and after working hours. Only one tenth ever received a grant for their work. These findings highlight that the key barriers for the performance of research are lack of time and funding. Psychiatric trainees and ECPs are motivated to perform research but need support and regular opportunities.